Analisa Keandalan Instrumentasi Boiler Feed Pump Menggunakan Metode Failure Mode and Effect Analysis (FMEA) di PT.PLN Nusantara Power UP Tenayan - S, Raehan Adillah; Jufrizel, Jufrizel; Maria, Putut Son; Zarory, Hilman (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
PT. PLN Nusantara Power UP Tenayan is a company operating in the power generation sector and focuses on operating PLTUs Tenayan, Indonesia. One part of the machine that influences the operation of the generator is the boiler feed pump. Lack of optimal boiler feed pump instrumentation often results in failure in operating activities. This research uses the Failure Mode and Effect Analysis (FMEA) method with the research objective of finding out the causes of failures that occur, identifying the type of failure, and determining the RPN value and the impact that occurs. The analysis results, it shows that the Boiler Feed Pump instrumentation components still meet operating standards because the Risk Priority Number (RPN) value is below 200, even though the Speed Sensor has a fairly high RPN value but is still in the reliable category, the result of identifying the type of failure that occurs is that the indicator reading is not actual, the component is not functioning, the highest RPN value for the Boiler Feed Pump component is the Speed Sensor component with an RPN value of 160 and the lowest RPN value is for the pressure indicator component with an RPN value of 30. The most important recommended action for the Speed Sensor component is to carry out maintenance for 1 month very.Keywords – Boiler Feed Pump, FMEA, Keandalan, Pembangkit, RPN.